Live attenuated influenza vaccine provides superior protection from heterologous infection in pigs with maternal antibodies without inducing vaccine associated enhanced respiratory disease - Vincent, Amy L.; Ma, Wenjun; Lager, Kelly M.; Richt, Juergen A.; Janke, Bruce H.; Sandbulte, Matthew R.; Gauger, Philip; Loving, Crystal L.; Webby, Richard J.; GarcÃa-Sastre, Adolfo (My University, 2012)
Control of swine influenza A virus (IAV) in the US is hindered since inactivated vaccines do not provide robust cross‐protection against the multiple antigenic variants co‐circulating in the field. Vaccine efficacy can be further limited when administered to young pigs that possess maternally derived immunity. We previously demonstrated a recombinant A/sw/Texas/4199‐2/1998 (TX98) (H3N2) expressing a truncated NS1 protein is attenuated in swine and has potential for use as an intranasal live attenuated influenza virus (LAIV) vaccine. In the present study, we compared 1 dose of intranasal LAIV with 2 intramuscular doses of TX98 whole inactivated virus (WIV) with adjuvant in weanling pigs with and without TX98‐specific maternally‐derived antibodies (MDA). Pigs were subsequently challenged with wild type homologous TX98 H3N2 virus or with an antigenic variant A/sw/Colorado/23619/1999 (CO99) (H3N2). In the absence of MDA, both vaccines protected against homologous TX98 and heterologous CO99 shedding, although the LAIV elicited lower hemagglutination inhibiting (HI) antibody titers in serum. The efficacy of both vaccines was reduced by the presence of MDA; however, WIV vaccination of MDA‐positive pigs led to dramatically enhanced pneumonia following heterologous challenge, a phenomenon known as vaccine‐associated enhanced respiratory disease (VAERD). A single‐dose of LAIV to MDA‐positive pigs still provided partial protection from CO99 and may be a safer vaccine for young pigs in field conditions where dams are routinely vaccinated and diverse IAV strains are in circulation. These results have implications not only to pigs but to other influenza virus host species.
Keywords: Swine influenza A virus; Influenza; Vaccine efficacy